The Implementation of Minimum Wages in Malaysia (Sains Humanika, 2014)
Minimum wage legislation is gazetted by government in order to protect low skilled employees in order to increase their quality of life and reduce poverty. In addition, it is also aimed at encouraging companies to increase the value chain by investing in new technologies that require less unskilled workers. The aim of the policy is undeniable noble but the impact of its implementation is still debateable. Some may question the adequacy of the minimum wage rate or may argue that the policy will induce the influx of illegal workers. Despite that, organizations have different approach in implementing the policy in order to achieve the best solutions. The new policy gives more financial burden on small and medium organizations as compared to large companies. Thus, small and medium enterprises (SMEs) were allowed to defer payment of minimum wage to foreign workers until December 2013. The objective of this study is to describe the implementation of minimum wage policy in Malaysia and compare the implementation of minimum wage legislation between China, South Africa and Brazil. This paper applies a comparative study by using round desk discussion and case-studies methods.Â
Keywords: Minimum wages; Small and Medium Enterprise (SME); foreign workers; full time and part time employment